EVALUATION OF EFFICACY AND SAFETY OF NIGELLA SATIVA OIL SUPPLEMENTATION IN PATIENTS OF CHRONIC KIDNEY DISEASE - Ansari, Zafar M; Nasiruddin, Mohammad; Khan, Rahat A; HAQUE, SHAHZAD F (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To evaluate efficacy and safety of add-on therapy of Nigella sativa oil in patients of stage 3 and 4 of chronic kidney disease (CKD). Materials and Methods: The study was conducted in a tertiary care center of north India in stage 3 and 4 patients of CKD. It was a prospective, comparative, and open label study. Patients were randomly divided into two interventional groups. Group I (Control) received conservative management of CKD while Group II (Test) received conservative management along with N. sativa oil (2.5 mL, per orally, once daily) for 12 weeks. Hemogram and renal function tests were done, and adverse events were recorded at 0, 6, and 12 weeks of treatment. Results: After 12 weeks of treatment, there was a progressive improvement in clinical features and biochemical parameters in both the groups, but it was more marked in the test group compared to control group. Both groups showed gradual improvement in the biochemical parameters as compared to their pre-treated values which were more marked in N. sativa oil supplemented group. There was a reduction in blood glucose, blood urea, serum creatinine, and 24-hr total urine protein. There was an increase in hemoglobin, 24-hr total urine volume, and glomerular filtration rate. Conclusion: N. sativa oil supplementation along with conservative management is efficacious and safe in averting the progression of disease in stage 3 and 4 patients of CKD. Keywords: Chronic kidney disease, Nigella sativa oil, End-stage renal disease, Glomerular filtration rate.